Age-related trends in anthropometry and jump and sprint performances in elite soccer players from 13 to 20 years of age: A cross-sectional study - Salinero, J. J.; Gonzalez-Millan, C.; Gutierrez, D.; Abian-Vicen, J.; Burillo, P.; Del Coso, J. (Journal of Human Sport & Exercise, 2019)
The aim of this investigation was to determine age-related trends for anthropometric and physical variables in elite young soccer players. For this purpose, a total of 114 young male soccer players from a high-performance soccer academy participated in this investigation. Anthropometric and physical variables (countermovement jump, 6×40 m shuttle run test, 2×11 m slalom test with the ball) were determined. Results. Body height (U15<U17~U20; p<0.01) and body mass significantly increased (U15<U17<U20; p<0.01) while body fat decreased with age (U15~U17>U20; p<0.01). However, the relationships of these variables with age were explained by curvilinear polynomial equations with a tendency for plateauing at ~17 years of age. There were also age-based differences in maximal running velocity (U15<U17<U20; p<0.01), running velocity with ball (U15<U17~U20; p<0.01) and jump height (U15<U17<U20; p<0.01). The relationships of the physical variables with age were explained by curvilinear polynomial equations with plateaus starting at~17 years of age. In young soccer players, the evolution of individual anthropometric and physical condition is strongly related to player`s age as part of the qualitative adaptations that accompany growth. However, the growth process cannot be explained by linear models because most of the variables reached a plateau when players were 17 years of age.